Urease active bio-slurry: a novel soil improvement approach based on microbially induced calcite precipitation - Cheng, L.; Shahin, Mohamed (NRC Research Press, 2016)
This paper presents a novel approach for soil stabilization by microbially induced carbonate precipitation (MICP) using a new urease active catalyzer, named herein as “bioslurry”. The bioslurry, which was produced from the reaction between bacterial culture and 400 mmol/L of CaCl2 and urea, is pre-formed urease active crystals consisting of CaCO3 plus imbedded urease active bacterial cells. By mixing the bioslurry with sand, more than 95% of the bioslurry was retained in the soil matrix as a result of the mechanical trapping mechanism, leading to high resistance to flushing with a low-salinity solution. The retained urease activity of bioslurry was uniformly distributed along the sand matrix, resulting in a rather uniform CaCO3 precipitation. Through repeated treatments with a cementation solution, the unconfined compressive strength of bioslurry treated sand was significantly improved due to the effective CaCO3 precipitation at the contact points of soil grains. Scanning electron microscopy analysis carried out on the bioslurry treated sand revealed that the induced large rhombohedral CaCO3 crystals were localized around the bioslurry spherical fine crystals. The overall outcome of this work is that soil biocementation using the new bioslurry approach is controllable, reproducible, and homogeneous.